NILAI-NILAI DAKWAH DALAM BUKU CATATAN UNTUK DIRIKU KARYA HAIDAR BAGIR - Tri Cahyo, Wisnu; Hamid, Abdul; Uyuni, Badrah (Spektra: Jurnal Ilmu-ilmu Sosial, 2022)
Da'wah values ​​are very important in the current era of globalization which tends to be destructive. One of the solutions from globalization is, da'wah bil Qalam is like a book. Through books, the values ​​of da'wah can be transmitted because books are a medium for conveying information and ideas from book authors in a comprehensive and in-depth manner. Da'wah bil Qalam through books has become a common thing done by preachers who deliberately write books about how a Muslim addresses life's problems, improves himself, and gains true happiness, such as the book Notes for Myself. The purpose of this research is to find out and describe the da'wah values ​​contained in the book Notes for Myself by Haidar Bagir. The type of research used in this research is library research with a qualitative approach. The primary data sources used were Notebooks for Myself and secondary data sources, namely books, journals, web articles and other literature. The data analysis used was Miles and Huberman's data analysis with data analysis activities: data reduction, data display, and conclusion drawing/verification.